Identifikasi Drug Related Problems (DRPs) Pada Pasien Congestive Heart Failure (CHF) Di Instalasi Rawat Jalan RSUD dr. Soekardjo Kota Tasikmalaya - Sinta Sri Nurfatwa; Eddy Suhardiana; Kamiel Roesman Bachtiar (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Research on the Identification of Drug Related Problems (DRPS) has been carried out in Congestive Heart Failure (CHF) patients at the Outpatient Installation of RSUD dr. Soekardjo City of Tasikmalaya used a descriptive method of medical record data of CHF patients retrospectively. This study aims to determine the frequency and categories of DRPs that occur based on the Pharmaceutical Care Network Europe V9.0 classification. The results showed that out of 80 patients, 288 DRPs were found consisting of 4 symptoms (indications) that were not treated (1.4%), adverse drug events may occur as much as 1 event (0.3%), inappropriate drug combinations or drug interactions as many as 279 events (96.9%), and the dose was too high in 4 incidents (1.4%), so that it can be concluded that the categories of causes and problems of DRPs that most often occur in RSUD dr. Soekardjo City of Tasikmalaya in 2022, namely drug interactions.